Early outcome of Lichtenstein technique for complete variety of inguinal hernia repair in a tertiary care hospital - Kabir, ASM Anwarul; Ahmad, Imtiaz; Sharmin, Mahbuba; Akhter, Khaleda; Hoq, Md Rashidul; Alam, Mohammad Shahidul (Northern International Medical College Journal, 2020)
Background: Inguinal hernia repair is very common in day to day general surgical practice. Result of surgical repair is often satisfactory but recurrences following surgery are troublesome both for the surgeon and the patient. Lichtenstein technique is now the most widely performed technique in groin hernia repair. Objective: The aim of this study was to assess short term outcome of complete variety of inguinal hernia repair by Lichtenstein technique. Methodology: This was a prospective observational study in which 30 complete variety of inguinal hernia repairs were performed by Lichtenstein technique between January 2014 and December 2017 by same surgical team in surgery department, Holy Family Red Crescent Medical College Hospital (HFRCMCH). Patients were scheduled for follow up visits at the end of first week, third month and sixth month after operation in out-patient department. The main outcome measures were postoperative complications, early recurrence, groin pain. Result: In this study age of the patients ranged from 30 years to 78 years, the mean age was 51.93 (±SD 10.12) years. Most of the hernia were of indirect type 18(60%) followed by direct type 9(30%). In indirect type (55.6%) of the hernias was right sided and the rest (44.4%) were left sided. On an average each operation lasted for 1.18 hours and oral feeding started 12.69 hours after the operation, Postoperative mean hospital stay that was 2.27 days. Postoperative complications were 2(6.7%) had a prolonged recovery and presented with abdominal distention after operation and 3(10%) patients developed postoperative urinary retention. Scrotal haematoma formation was observed in 2(6.7%) cases and other post-operative complications were local haematoma or seroma formation in incision site, periincisional skin echymosis, postoperative pyrexia, superficial wound infection and post-operative pain were found in 1 (3.3%) cases. Regarding outcome no recurrence or mesh rejection or mesh infection were observed within short time postoperative follow up period. Conclusion: In this study no recurrence or mesh rejection or mesh infection were observed within short time postoperative follow up period and patient's compliance was good with minimum morbidity. Therefore, Lichtenstein's technique of inguinal hernia repair considered as a safe and effective procedure. Northern International Medical College Journal Vol.10 (2) Jan 2019: 389-392